Baby Santa's music box - Aigner-Clark, Julie; Baby Einstein Company (United States] Disney DVD ; $a Burbank, CA Distributed by Buena Vista Home Entertainment, 2000)
Watch Baby Santa's Music Box featuring a magical excursion of lights, ornaments, sleigh bells, stockings, presents, winter scenes, happy children and jolly Santas. Or listen to the Baby Einstein Music Box Orchestra for a holiday classics concert of traditional melodies from France, England, Ireland, Germany, Israel, Japan and the U.S., plus classical favorites by Handel, Mozart, and Tschaikovsky
A joyous celebration of holiday magic through the eyes and ears of a child"--Container
1
Keywords: Christmas -- Juvenile films; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs